In the service of his Korean majesty: William Nelson Lovatt, the Pusan Customs, and Sino-Korea relations, 1876-1888 - Patterson, Wayne (Institute of East Asian Studies, University of California, 2011)
"This book, based upon the correspondence of William Nelson Lovatt, Korea's first commissioner of customs in Pusan, looks at the informal imperialism exercised by China over Korea in the 1880s, as China's increasing interventionism affected Lovatt's hiring, his experiences in Korea, and his eventual termination"--Provided by publisher.
Includes bibliographical references and index.
"This book, based upon the correspondence of William Nelson Lovatt, Korea's first commissioner of customs in Pusan, looks at the informal imperialism exercised by China over Korea in the 1880s, as China's increasing interventionism affected Lovatt's hiring, his experiences in Korea, and his eventual termination"--Provided by publisher.
Keywords: Customs administration / Korea / History / 19th century.; Pusan (Korea) / Social life and customs.; Korea / Foreign economic relations / China / History.; China / Foreign economic relations / Korea / History.